2011
DOI: 10.1508/cytologia.76.177
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of Gametophytic Cells and Identification of Their Cell-Specific Markers in Torenia fournieri, T. concolor and Lindernia micrantha

Abstract: Summary Gametophytic cells in the female embryo sac, the egg, the central and the synergid cells have unique roles in sexual reproduction in higher plants. To investigate their cell-specific features, an efficient method of distinguishing and isolating each gametophytic cell is required. By testing the activities of several cellulase enzymes, we modified our previous cell isolation method and succeeded in isolating each cell from the Torenia and Lindernia species. We also established genetic markers that show … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
2
1
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…cDNA was synthesized using SuperScript w reverse transcriptase (Invitrogen, Carlsbad, CA, USA). The expression of cell-type specific marker genes in these mRNAs (Kawano et al, 2011) was confirmed to clarify that no contamination of other cell types in the pool of synergid cell mRNA and egg cell mRNA. TcCRP1 was first isolated from ovule cDNA by PCR using gene-specific degenerate primers (Supplementary Data Table S1, available online).…”
Section: Rna Isolation the Cloning Of Tccrp1 And Rt-pcrmentioning
confidence: 93%
“…cDNA was synthesized using SuperScript w reverse transcriptase (Invitrogen, Carlsbad, CA, USA). The expression of cell-type specific marker genes in these mRNAs (Kawano et al, 2011) was confirmed to clarify that no contamination of other cell types in the pool of synergid cell mRNA and egg cell mRNA. TcCRP1 was first isolated from ovule cDNA by PCR using gene-specific degenerate primers (Supplementary Data Table S1, available online).…”
Section: Rna Isolation the Cloning Of Tccrp1 And Rt-pcrmentioning
confidence: 93%
“…In most studies, female gametophyte cells were isolated with the enzyme solution containing cellulase. The optimized conditions of the enzyme solution were different for different plant species (Kawano et al, 2011). The cell-type specific RNA-seq, including the mutants defective in female gametophyte cell function, must be powerful tools to reveal the precise gene expression changes associated with each cell functions or specifications.…”
Section: Introductionmentioning
confidence: 99%